AI 2017 : advances in artificial intelligence : 30th Australasian Joint Conference, Melbourne, VIC, Australia, August 19-20, 2017, Proceedings /: advances in artificial intelligence : 30th Australasian Joint Conference, Melbourne, VIC, Australia, August 19-20, 2017, Proceedings. (2017) - Unknown
No abstract available